Characterising the stiffness and hysteresis of single and dual truck tyres - Magweba, Thabani Tafadzwa (My University, 2019)
High body accelerations in heavy vehicles can result in discomfort, injury and damage to freight. In combination with the suspension, a tyre absorbs road shocks for the comfort of the driver and passengers and ensures the integrity of freight. Heavy vehicles make use of either single or dual truck tyres. The two configurations possess different stiffness and hysteresis or damping characteristics. These stiffness and hysteresis characteristics influence the body accelerations experienced (i.e. the ride). The purpose of this research project was to characterise and compare the stiffness and hysteresis of single and dual truck tyres. Previous research has modelled tyres as a simple spring and damper and as a rigid or flexible ring connected to the hub with spring and damper elements with no hysteresis in both cases. Models such as the FTire and SWIFT models can model hysteresis but are complicated, have numerous parameters and require the purchase of expensive software. A custom-built rolling road rig was employed to measure the tyre deflections and corresponding loads of a Dunlop 385/65 R22.5 single tyre and Dunlop 315/80 R22.5 dual tyres. A tyre model was developed which included a characteristic deflection term to model hysteresis. The model was verified and its parameters validated using static load-deflection tests, dynamic load-deflection tests and stepped load response tests. The results confirmed that tyres exhibit hysteresis and the proposed model fitted the experimental data well. It was shown that tyres possess a characteristic deflection which is a measure of the spatial rate at which the force versus displacement response transitions into a linear response. The dual configuration has a higher average stiffness (loading - 2.550 kN/mm, unloading - 2.032 kN/mm) than the single configuration (loading - 1.859 kN/mm, unloading - 1.553 kN/mm). When loading, the average characteristic deflection was calculated to be~= 0.02403 mm (single), ~ = 0.02901 mm (dual) and when unloading~= 0.02349 mm (single),~= 0.02976 mm (dual).
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Engineering to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, 2019